Advances in Interfaces between Li Metal Anode and Electrolyte. Issue 2 (1st December 2017) - Zhang, Xue‐Qiang; Cheng, Xin‐Bing; Zhang, Qiang
Abstract: Lithium metal has been considered as one of the most promising anode materials in high‐energy‐density rechargeable batteries due to its extremely high specific capacity and very low reduction potential of all possible candidates. However, the mysterious interfacial phenomena of lithium metal anode in long‐term cycles, especially Li dendrite formation and low Coulombic efficiency, have greatly plagued the practical applications of Li metal in secondary batteries. The complex interface between Li metal and electrolyte plays a very important role in regulating Li deposition and enhancing the cycling stability of a full battery. In this review, recent advances in interfacial science and engineering are summarized to afford a fundamental understanding in Li deposition behavior and present design principles in constructing robust interface to stabilize Li metal anode in a working battery. Further investigations and directions are also included to promote the exploration of Li metal anodes. In particular, the rational combination of different Li metal protection strategies is strongly commended for practically applying Li metal anode in high‐energy‐density rechargeable batteries. Abstract : The interfacial science and engineering of Li metal anode and electrolyte are summarized to afford a fundamental understanding in Li deposition behavior and present design principles in constructing robust interface to stabilize Li metal anode in a working battery. The rational combination of different Li metal protection strategies is strongly commended for their practical applications in high‐energy‐density batteries.